The effect of elevated blood cortisol levels on the extinction of a conditioned stress response in rainbow trout - Barreto, R. E.; Volpato, G. L.; Pottinger, T. G. (Elsevier B.V., 2006)
Following previously published observations that a conditioned response (CR) was lost more quickly by rainbow trout (Oncorhynchus mykiss) exhibiting a high responsiveness to stressors than by low responding individuals this study was designed to investigate the effects of exogenous cortisol on the retention of a CR in unselected rainbow trout. Fish held in isolation were conditioned over a 10-day period by pairing an innocuous signal (conditioned stimulus, CS: a water jet played on the surface of the tank water) with a mild stressor (unconditioned stimulus, US: 30 min of confinement). This resulted in a brief elevation of plasma cortisol levels (the CR) when the fish was exposed to the CS only. The effect of exogenous cortisol on the retention of the CR was evaluated by comparing the performance of fish that received cortisol-containing slow-release intraperitoneal implants, with fish receiving vehicle-only implants. Retention of the CR was assessed at intervals up to 35 days after conditioning ceased. The CR was considered to be evident when 30 min following presentation of the CS, mean plasma cortisol levels were significantly higher in conditioned than untrained fish. on day 1 both cortisol-implanted and vehicle-implanted conditioned fish exhibited a CR. However, from day 5 onwards the CR was observed only in the vehicle-implanted and conditioned group. This finding indicates that administration of cortisol accelerated the extinction of the CR in the cortisol-implanted fish, suggesting that elevated plasma cortisol levels can impair memory processes in rainbow trout. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: stress; exogenous cortisol; memory; Pavlovian conditioning; Oncorhynchus mykiss; fish